2018
DOI: 10.1101/346833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capturing variation impact on molecular interactions: the IMEx Consortium mutations data set

Abstract: The current wealth of genomic variation data identified at the nucleotide level has provided us with the challenge of understanding by which mechanisms amino acid variation affects cellular processes. These effects may manifest as distinct phenotypic differences between individuals or result in the development of disease. Physical interactions between molecules are the linking steps underlying most, if not all, cellular processes. Understanding the effects that amino acid variation of a molecule's sequence has… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This is achieved by predicting one of the following as the outcome of the mutation effect type on PPI: strengthens the interaction (“increasing”), reduces the interaction (“decreasing”), suspends the interaction (“disrupting”), and does not affect the interaction (“no effect”). These 4 types of mutation effects were defined by the IMEx dataset [ 21 ] (Fig. 1 A, released version: 2020 May 20), which contained a set of experimentally validated variant impacts on molecular interactions ( N = 28,000).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is achieved by predicting one of the following as the outcome of the mutation effect type on PPI: strengthens the interaction (“increasing”), reduces the interaction (“decreasing”), suspends the interaction (“disrupting”), and does not affect the interaction (“no effect”). These 4 types of mutation effects were defined by the IMEx dataset [ 21 ] (Fig. 1 A, released version: 2020 May 20), which contained a set of experimentally validated variant impacts on molecular interactions ( N = 28,000).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the IMEx dataset [ 21 ] was manually curated from thousands of experimental studies under various conditions, there might be different mutation effects reported in IMEx for the same PPI carrying the same missense mutation. Thus, we excluded this type of entry with multiple mutation effect annotations from the preprocessing step before constructing the MIPPI model (see Table S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations